Conceptualizing the Public Component of Green Finance - Horyn Volodymyr P.; Sydor Iryna P.; Bula Pavlo V.; Mudryi Taras P. (Problemi Ekonomiki)
The article presents a theoretical substantiation for the public component of green finance. The generalization of scientific viewpoints from domestic and foreign economic science regarding the essence and structure of green finance has enabled the distinction of both public and private components within it. The public component of green finance encompasses financial relationships involving the State, which accompany the formation and utilization of financial resources for the implementation of ecological sustainable development goals. Both general and specific characteristics of public green finance are disclosed, along with the principles of their operation, which include imperativeness, strategic orientation, and the alignment of interests (inclusiveness). Particular attention is given to uncovering the main features of the instruments of green finance that public authorities use in the formation and utilization of financial resources for the realization of the ecological component of sustainable development goals. According to the nature of the action, these instruments are classified into fiscal, regulatory, and universal. Financial instruments of public green finance have also been proposed to be distinguished according to the content of operations in which they are involved (when forming or using financial resources), but a characteristic feature of some such instruments (grants, green loans) is their universality. Key features and problematic aspects of environmental taxation, the implementation of a greenhouse gas emissions trading system, and innovative schemes for converting State debt obligations in exchange for funding green projects are characterized. It is substantiated that under wartime conditions, budgetary programs related to the sphere of green finance have not only environmental but also security significance, aimed at reducing Ukraine’s dependence on imported energy resources and maintaining the country’s energy system in a functional state. Prospects for further research on the theoretical substantiation of public green finance lie in examining the external environmental factors that influence the parameters of their development, as well as developing formalized approaches to assess the impact of public finance instruments on the indicators of the country’s ecological development.